Elimination of Radiation-Induced Senescence in the Brain Tumor Microenvironment Attenuates Glioblastoma Recurrence - Fletcher-Sananikone, Eliot; Kanji, Suman; Tomimatsu, Nozomi; Cristofaro, Luis Fernando MacEdo Di [UNESP]; Kollipara, Rahul K.; Saha, Debabrata; Floyd, John R.; Sung, Patrick; Hromas, Robert; Burns, Terry C.; Kittler, Ralf; Habib, Amyn A.; et al. (American Association for Cancer Research (AACR), 2021)
Glioblastomas (GBM) are routinely treated with ionizing radiation (IR) but inevitably recur and develop therapy resistance. During treatment, the tissue surrounding tumors is also irradiated. IR potently induces senescence, and senescent stromal cells can promote the growth of neighboring tumor cells by secreting factors that create a senescence-associated secretory phenotype (SASP). Here, we carried out transcriptomic and tumorigenicity analyses in irradiated mouse brains to elucidate how radiotherapy-induced senescence of non-neoplastic brain cells promotes tumor growth. Following cranial irradiation, widespread senescence in the brain occurred, with the astrocytic population being particularly susceptible. Irradiated brains showed an altered transcriptomic profile characterized by upregulation of CDKN1A (p21), a key enforcer of senescence, and several SASP factors, including HGF, the ligand of the receptor tyrosine kinase (RTK) Met. Preirradiation of mouse brains increased Met-driven growth and invasiveness of orthotopically implanted glioma cells. Importantly, irradiated p21_/_ mouse brains did not exhibit senescence and consequently failed to promote tumor growth. Senescent astrocytes secreted HGF to activate Met in glioma cells and to promote their migration and invasion in vitro, which could be blocked by HGF-neutralizing antibodies or the Met inhibitor crizotinib. Crizotinib also slowed the growth of glioma cells implanted in preirradiated brains. Treatment with the senolytic drug ABT-263 (navitoclax) selectively killed senescent astrocytes in vivo, significantly attenuating growth of glioma cells implanted in preirradiated brains. These results indicate that SASP factors in the irradiated tumor microenvironment drive GBM growth via RTK activation, underscoring the potential utility of adjuvant senolytic therapy for preventing GBMrecurrence after radiotherapy. Significance: This study uncovers mechanisms by which radiotherapy can promote GBM recurrence by inducing senescence in non-neoplastic brain cells, suggesting that senolytic therapy can blunt recurrent GBM growth and aggressiveness. _2021 American Association for Cancer Research.